2020
DOI: 10.1097/md.0000000000020764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yijinjing exercise on cervical spondylosis

Abstract: Background: Cervical spondylosis (CS) is a common disease due to the modern lifestyle. Yijinjin, a kind of traditional Chinese exercise, is frequently used for the prevention of CS by Traditional Chinese Medicine doctors. However, there is no relevant systematic review show its effectiveness and safety. The study aims to evaluate the effectiveness and safety of Yijinjing for patients with CS. Methods: The following electronic databases will be searched from the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Nonspecific chronic neck pain is a clinical syndrome with high morbidity and recurrence rates, and complementary and alternative comprehensive therapies are recommended for its management. As traditional Chinese physical therapies, tuina and yijinjing are widely used in neck pain, which may explain the high patient adherence in this randomized clinical trial, with no dropout cases.…”
Section: Discussionmentioning
confidence: 92%
“…Nonspecific chronic neck pain is a clinical syndrome with high morbidity and recurrence rates, and complementary and alternative comprehensive therapies are recommended for its management. As traditional Chinese physical therapies, tuina and yijinjing are widely used in neck pain, which may explain the high patient adherence in this randomized clinical trial, with no dropout cases.…”
Section: Discussionmentioning
confidence: 92%
“…This condition is particularly prevalent among middle-aged and older individuals [3], [4]. Given the aging population, rehabilitation for cervical spondylosis has become a prominent concern in the medical field [5], [6], [7], [8]. Research conducted in traditional Chinese medicine has confirmed that appropriate massage techniques (Tuina therapy) can effectively improve the relief of neck muscle spasms, facilitate the restoration of physiological curvature and dynamic balance of the cervical spine, and ultimately contribute to the rehabilitation process of individuals with cervical spondylosis [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%